2004
DOI: 10.1021/nl048326j
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymer Translocation with Single-Walled Carbon Nanotubes

Abstract: The translocation of single-walled carbon nanotubes (SWNTs) across MCF7 breast cancer cells was demonstrated with radioisotope labeling. Hybrids of SWNT−RNA polymer poly(rU) were formed through a nonspecific binding mechanism which could allow for the dissociation of the poly(rU) from the SWNTs upon delivery. The cellular uptake of the hybrids was examined by confocal fluorescence microscopy. Through cell growth and MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
198
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(204 citation statements)
references
References 22 publications
4
198
1
1
Order By: Relevance
“…Because of their unique physical and chemical properties, nano-materials have great potential use in agriculture, computer, medicine, military and many other areas. Simultaneously, it has been recognized that because of their ultrafine particle size, nano-materials can enter cells or even cross the blood-brain carrier [1][2][3] and cause harm to organisms. Much research has been done to investigate the toxicity of nano-materials on organisms [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their unique physical and chemical properties, nano-materials have great potential use in agriculture, computer, medicine, military and many other areas. Simultaneously, it has been recognized that because of their ultrafine particle size, nano-materials can enter cells or even cross the blood-brain carrier [1][2][3] and cause harm to organisms. Much research has been done to investigate the toxicity of nano-materials on organisms [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering in vitro studies have shown that SWNTs and SWNHs can be used to deliver therapeutic drugs and diagnostic molecules into cells (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Carbonaceous tubules absorb light in the near-infrared region, and can cause cell death by a localized photothermal or photohyperthermia (PHT) effect (14).…”
mentioning
confidence: 99%
“…46,49,50 Among nanomaterials, CNTs are known as effective transporters of biological macromolecules and drugs to target cells and tissues. 4,6,[17][18][19][20][21][22][23][24] However, this type of medical application implies intravenous administration and translocation into to the blood circulation. Therefore, this study investigated whether MWCNTs produce cytotoxic and genotoxic effects in healthy HPBLs.…”
Section: Discussionmentioning
confidence: 99%
“…16 The CNTs could be adsorbed or conjugated with various therapeutic molecules such as peptides, proteins, DNA, RNA, and drugs. 4,6,7,[17][18][19][20][21][22][23][24] The CNT-bioactive molecule complex has been proven to be an excellent vehicle for drug delivery by penetrating into cells and keeping the drug from being metabolized during transport. [25][26][27][28] However, these medicinal findings are in an experimental stage and are still not applied to human medicine.…”
Section: Introductionmentioning
confidence: 99%